Comparing Long-Term Unemployment, Secondary Labor Markets and Household Incomes - Pekka Kosonen; Pasi Moisio (Luxembourg Income Study (LIS), 1999)
The purpose of this paper is to compare the groups of the unemployed, low-paid workers and precarious/part-time workers; and their families' disposable incomes. Comparable data from three countries, i.e. Finland, Germany and the United Kingdom is used.
Keywords: 330; Langzeitarbeitslosigkeit; Zweiter Arbeitsmarkt; Haushaltseinkommen; Soziale Isolation; Deutschland; Finnland; Großbritannien